1998
DOI: 10.1017/s0007114598001536
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal degradation in pigs of rye dietary fibre with different structural characteristics

Abstract: In order to investigate the effects of dietary fibre (DF) characteristics on carbohydrate degradation and the metabolism in the large intestine, pigs were fed on four rye-bread diets (based on whole rye, pericarp/testa, aleurone or endosperm) with differences in characteristics and amount of DF. The degradability of DF in the large intestine varied greatly between diets. The pericarp/testa DF was hardly degraded in the large intestine, whereas endosperm DF was extensively and rapidly degraded in the caecum. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
61
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 39 publications
15
61
0
Order By: Relevance
“…6 The release of carbohydrates causes a delay in the fermentation process, as shown in this study: a soluble rye bran extract was fermented rapidly and the other substrates containing undegraded cell-wall tissues were fermented slowly. This is in accordance with the results of Glitsø et al 30,31 Xylanase treatment of rye bran made the carbohydrates of cell-wall structures more accessible to colonic microbiota and thus increased the initial rate of fermentation (Fig 2c). Xylanase treatment, however, hydrolysed cell walls only partly, because the consumption of carbohydrates of xylanase-treated rye bran was very similar to that of extruded rye bran.…”
Section: Discussionsupporting
confidence: 92%
“…6 The release of carbohydrates causes a delay in the fermentation process, as shown in this study: a soluble rye bran extract was fermented rapidly and the other substrates containing undegraded cell-wall tissues were fermented slowly. This is in accordance with the results of Glitsø et al 30,31 Xylanase treatment of rye bran made the carbohydrates of cell-wall structures more accessible to colonic microbiota and thus increased the initial rate of fermentation (Fig 2c). Xylanase treatment, however, hydrolysed cell walls only partly, because the consumption of carbohydrates of xylanase-treated rye bran was very similar to that of extruded rye bran.…”
Section: Discussionsupporting
confidence: 92%
“…Although different types of bread differed substantially in their amounts of dietary fibre compounds (Table 2), no significant differences of faecal bacteria profiles and cell counts in the fermentation solids of bread samples were observed in this study (results not shown), an aspect which was also reported by Gråsten et al (2007) for postmenopausal women after dietary intervention with low-or high-fibre bread. Anyhow, the likely prebiotic properties of bread samples observed in this study were also suggested for different cereals and cereal milling fractions in human intervention trials (Constabile et al, 2008) and animal studies (Canzi et al, 1994;Glitsø, Brunsgaard, Højsgaard, Sandström, & Bach Knudsen, 1998). Vardakou et al (2008) observed that particularly the insoluble wheat arabinoxylans induce xylanase and ferulic acid esterase activities of faecal anaerobes in human intestinal model systems.…”
Section: Dietary Fibre Degradation Analysissupporting
confidence: 66%
“…Due to their structural characteristics, dietary fibre (DF) influences digestion and absorption processes along the gastrointestinal (GI) tract (Glitsø et al, 1999). Arabinoxylans, the most important DF of cereals, represent a heterogenic group of polysaccharides of high molecular weight which are comprised of xylan backbones substituted to various degrees with arabinose residues (Fincher and Stone, 1986) according to grain tissues and botanical origins.…”
Section: Introductionmentioning
confidence: 99%